A Importância do Conhecimento Científico na Educação Escolar: Contribuições da Pedagogia Histórico-Crítica - Chaves, Isis de Azevedo (2021)
In this work, a reflection on the origin, social function and nature of scientific knowledge and its importance for school education in the light of Historical-Critical Pedagogy is socialized. The devaluation of scientific knowledge is problematized and it is explained that this type of knowledge can greatly contribute to the social function of school education, that is, allow students to have a solid understanding of social reality, in a perspective that goes beyond appearances. Based on the understanding of Historical-Critical Pedagogy that educational work is the act of producing the human in man, three specific objectives were defined: first, to elucidate the origin and human formation and the specificity of scientific knowledge for humanity; second, to demonstrate the origin and social function of school education under a historical-critical perspective; and, third, to present Historical-Critical Pedagogy as the pedagogy that defends the intellectual and human development of individuals, and insists on proving the humanist inseparability between science and school and defending the right of the working class to have access to classical knowledge, sciences, arts and philosophy. It is a research with a qualitative approach, of a theoretical nature. The methodological procedures adopted were literature review and immanent reading. It seeks to conceptualize and emphasize the importance of scientific knowledge, as well as school education. Therefore, it is intended to contribute to the understanding that the appropriations of scientific knowledge, specifically school, enable the development of the human psyche, which, in turn, refers to possibilities for the realization of human autonomy, the formation of the concrete subject, critical, capable of evaluating and transforming their own objective conditions. This qualitative development is what must be provided to the subject, in school education, in order for knowledge to be converted into learning with the intention of humanization. Keywords: School Education. Scientific knowledge. Historical-Critical Pedagogy